The effect of bio-banding on between-player variance in size and speed in male academy soccer players - Johnson, D.; Bradley, B.; Williams, S.; Whiteside, E.; Cumming, S. P. (Sport Performance & Science Reports, 2022)
Bio-banding groups young athletes based upon maturity rather than age and has shown benefits to academy footballers' development by reducing maturity associated variation in games. The main practical applications of this study are that when grouping players by maturity status (percentage of adult height) can reduce the variation in height, mass and momentum for adolescent soccer players. Aim: This study aimed to examine the extent to which grouping players using by maturity status (bio-banding) in comparison to age groups would reduce variation in physical paraeters of size, speed and momentum in a sample of academy soccer players. This aims to help give greater context around the strategy of bio-banding and give practical insights into the benefits of grouping players by maturity.